Hybrid renewable mini-grids on non-interconnected small islands: Review of case studies - Eras Almeida, Andrea A.; Egido Aguilera, Miguel Ángel (Renewable and Sustainable Energy Reviews, 2019)
Most small islands, with populations of between 1000 and 100,000 inhabitants, have non-interconnected power generation systems consisting of thermal power plants. This affects their ecological balance and implies a financial dependency on the price of fossil fuels and high electricity generation costs. However, small islands can accelerate their energy transition to become lower-carbon economies thanks to their enormous renewable energy potential. This research presents the current state of the art of hybrid renewable mini-grids (HRMGs) on non-interconnected small islands. To do so, a comparative analysis was applied among islands located in the Atlantic and Arctic, Pacific and Indian Oceans, and the Caribbean and Mediterranean Seas based on an extensive review of the literature. This study identifies business models applied to support the introduction of renewable energy and the key factors for the implementation of HRMGs on small islands. This review highlights how developed islands are successful in achieving their ambitious renewable energy targets. On the other hand, it is demonstrated that the least developed islands from the Pacific and Indian Oceans need to strengthen their weak regulatory frameworks and define suitable business models to promote renewable energy projects, involving private entities. Furthermore, these islands should find alternative funding sources apart from foreign aid. Developing islands should guide international cooperation in favor of effective policies and fostering local capacities. In those regions, thanks to the low prices of renewable technologies, the most attractive mechanisms for the implementation of HRMGs are the Renewable Energy Service Company model, competitive auctions and tax incentives.